Pengaruh Perbedaan Bobok Awal Terhadap Pertumbuhan Rumput Laut (Kappaphycus alvarezii) Menggunakan Metode Long Line di Perairan Kelapa Lima, Kupang - Felycia Anggrainy Olla; Aryok Nomleni; Debora Victoria Liubana (Lembaga Teewan Journal Solutions, 2026)
Kappaphycus alvarezii is an economically important seaweed widely cultivated as a source of carrageenan. This study examined the effect of different initial seedling weights (50 g, 100 g, and 150 g) on the growth performance of K. alvarezii cultivated using the long-line method in the waters of Kelapa Lima, Kupang, for 28 days. A descriptive quantitative approach was employed with 30 seedlings, consisting of 10 seedlings for each treatment. Growth performance was evaluated through absolute growth and specific growth rate (SGR). The results showed that all treatments experienced weight increases during the cultivation period. The highest absolute growth was recorded in the 150 g treatment (515.5 g), followed by the 100 g treatment (421 g) and the 50 g treatment (232.1 g). However, the highest SGR was observed in the 50 g treatment at 6.17% per day, followed by the 100 g treatment at 5.89% per day, while the 150 g treatment produced the lowest SGR at 5.32% per day. Water quality remained stable and suitable for seaweed cultivation, with average values of 30.4°C temperature, 33.8 ppt salinity, and pH 7.8, meeting SNI 8228.2-2015 standards. The study concludes that larger seedlings produce greater biomass accumulation, whereas smaller seedlings exhibit faster relative growth rates.